RETRACTED: Empirical analysis of the integration mechanism of explicit and implicit education on the ideological and political education and impact on mental health: The perspective of new media - Hui, Dong (Frontiers in Public Health, 2022)
Background Education nowadays should be a combination of explicit and implicit education, which can effectively improve the effectiveness of ideological and political education, promote the development of ideological and political education in universities, and ensure the quality of ideological and political education in universities. This study makes an empirical analysis of the integration mechanism of explicit education and implicit education of ideological and political education from the perspective of new media. Materials and methods A total of 1,050 students were included from the polytechnic university of China in the analysis. Questions regarding age, sex, source of information collections, Internet time, type of browsers used, and the influence of the Internet were asked of the students. The nine-item Patient Health Questionnaire was administered to measure the students' depressive symptoms. A comprehensive study was done to prove the depressive symptoms in students from the perspective of new media. Results A total of 78 % of students collected information from the Internet, and 1 % of students collected information from books. Most of the students spent more than 1 h on the Internet per day. It was concluded from the data that 245 college students were always influenced by the Internet, accounting for 24%, and 730 college students were occasionally influenced by the Internet, accounting for 73%. Forty-two college students do not influence the Internet, accounting for 4%. It can be seen that 95.6% of college students will be affected by the Internet compared with those who will never be affected by the Internet. Therefore, the new media network has high popularity among college students, as online time accounts for a large proportion of their study time. Conclusion From the perspective of new media, the integration of explicit and implicit education in ideological and political education is feasible. In today's information age, education implementers need to use a large number of new media images to enable students to accept education in the integration mechanism. From the perspective of new media, it is also necessary to innovate the forms of reports, establish the integration mechanism of explicit education and implicit education, strengthen educational links and interactive exchanges, and promote university education.